Evaluation of Leucaena varieties for fodder and fuel wood production in semi-arid regions - Singh, Ateet Pal; Kumar, Nilay; ., Sushma (Indian Journal of Agroforestry, 2020)
Leucaena the "miracle tree" of 1970s and early 1980s is gaining popularity due to its worldwide success as a long lived highly nutritious forage tree and its great variety of other uses like fuel wood, small timber and pulpwood. The objective of this study was to evaluate the best variety for fodder and fuel wood during scarcity season in semi-arid regions. Ten varieties of Leucaena were studied on the basis of biomass production viz. El-Salvador, K-8, K-23, K-29, K-585, K-601, S-22, S-24, K-156 and K-743A. Out of which variety K-23 and K-8 were found to perform best giving maximum leaf biomass (fodder) and shoot biomass (fuelwood). These varieties can be used to improve the quality and quantity of fodder and fuel wood during scarcity season and also ameliorate soil condition by adding Nitrogen through Nitrogen fixation.